(untitled) (Bangladesh Journal of Urology, 2023)
Introduction: Radical nephroureterectomy with excision of ipsilateral bladder cuff is the gold standard treatment for high risk upper urinary tract transitional cell carcinoma. This procedure requires two incisions. However endoscopic detachment of distal ureter and bladder cuff by transurethral incision and removal of kidney requires single abdominal incision. Though the intention is to decrease morbidity by avoiding a second lower abdominal incision, argument exists regarding oncological outcome Methods: This Quasi-Experimental study was conducted from September, 2020 to August, 2022 in the department of urology, Bangabandhu Sheikh Mujib Medical University. Here 15 patients were in Group A who underwent transurethral incision around the ureteric orifice to remove the bladder cuff (Pluck technique) with single abdominal incision for open radical nephroureterectomy and 17 patients were in Group B who underwent open extravesical approach for excision of cuff of bladder during radical nephroureterectomy making two abdominal incisions. Both techniques were compared to assess the operative and oncological outcome. Results: Operative time was longer in group B (p<0.001). Post-operative pain was more in group B (p<0.001), median duration of catheterization was 10 days in group A and 7 days in group B (p<0.001). Median duration of hospital stay 7 days in group A and 8 days in group B (p<0.069). In both group no patient had recurrence of TCC in urinary bladder at 3 months. However at 6 months 3 (20%) patients in group A and 2 (11.76%) patients in group B had recurrence of TCC in urinary bladder (p=0.645). In group A 1 (6.7%) patient had metastasis in pelvic cavity at 6 months postoperatively. But no patient in group B had metastasis in pelvic cavity (p=0.469). Conclusion: Transurethral incision around the ureteric orifice up to perivesical fat followed by extraction of distal ureter and bladder cuff by pluck technique is technically feasible and oncologically safe operation with a shorter operative time, less postoperative pain but need longer duration of catheterization and drain. Bangladesh J. Urol. 2023; 26(2): 70-77